2015
DOI: 10.1039/c5ra11577a
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced corrosion performance of Zn coating by incorporating graphene oxide electrodeposited from deep eutectic solvent

Abstract: In this work, novel zinc-graphene oxide (Zn-GO) composite coatings were successfully prepared by pulse electrodeposition in choline chloride (ChCl)/urea based deep eutectic solvent (DES). The GO sheets exhibited excellent dispersion stability in ChCl : 2urea DES without stabilizing additives and were uniformly deposited in the Zn matrix. The surface morphology and textured structure of the Zn-GO composite coatings were quite different from those of pure Zn coating, owing to the effects of GO on the electrochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 42 publications
3
33
0
Order By: Relevance
“…An effective way to evaluate the corrosion resistance of organic coating is EIS characteration. It is known that the impedance value at low frequencies in the Bode plot is always used to evaluate the corrosion resistance of the coatings [35,36]. The higher the value of impedance is, the higher the corrosion resistance.…”
Section: Eis Characterizationmentioning
confidence: 99%
“…An effective way to evaluate the corrosion resistance of organic coating is EIS characteration. It is known that the impedance value at low frequencies in the Bode plot is always used to evaluate the corrosion resistance of the coatings [35,36]. The higher the value of impedance is, the higher the corrosion resistance.…”
Section: Eis Characterizationmentioning
confidence: 99%
“…Owing to the similar properties to graphene and availability of less equipment-intensive chemical methods for producing large quantities of GO by oxidation of low cost and abundant graphite powder [23,24], GO has been used as a reinforcement to fabricate corrosion resistant metal matrix composite coatings. In fact, related research results have already shown that GO as second-phase material improves mechanical, thermal, and electrical properties of metal matrix materials [13,[25][26][27].…”
Section: Introductionmentioning
confidence: 98%
“…Preparation methods of metal matrix composite coatings include chemical vapor deposition method [22], the chemical reduction method [23], and the electrochemical deposition method [13,26,27]. Compared to the above-mentioned methods, the direct current electrodeposition technique has been broadly used because of its simple preparation equipment, easy operation, low cost, and easy industrialized promotion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 However, pure PANi nanollers oen have problems such as poor solubility and poor interfacial adhesion, which greatly affect the corrosion resistance of coatings. To address this issue, several strategies have been adopted in recent years, including the incorporation of soluble functional groups into the side chain, [27][28][29][30] the selection of appropriate dopants [31][32][33][34][35] and composite preparation with other well-dispersed nanoparticles.…”
Section: Introductionmentioning
confidence: 99%